2020
DOI: 10.1007/s10592-020-01320-3
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics of yellow-bellied toads (Bombina variegata): a matter of geographical scale and isolation

Abstract: Amphibian populations world-wide are threatened by declines and extinctions mainly due to habitat loss and fragmentation. Habitat fragmentation threatens the yellow-bellied toad Bombina variegata in the northern and western regions of its distribution where it is strictly protected. We studied the genetic structure and diversity of populations at three geographical scales using microsatellite loci to detect potential threats for population persistence. At the local scale, we sampled four neighbouring localitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…However, few of the 1,564 Natura 2000 sites intended to protect B. variegata are actually focused on the protection of this species. Whereas in western Europe the species is Critically Endangered (Kuzmin et al, 2009; Heatwole & Wilkinson, 2013; Hantzschmann et al, 2021), its status in the eastern part of the EU is regarded as favourable; but this is not so. In only two of the seven EU countries where the overall status of B. variegata was evaluated is its status favourable; in the other five the assessment is negative (European Environment Information and Observation Network, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, few of the 1,564 Natura 2000 sites intended to protect B. variegata are actually focused on the protection of this species. Whereas in western Europe the species is Critically Endangered (Kuzmin et al, 2009; Heatwole & Wilkinson, 2013; Hantzschmann et al, 2021), its status in the eastern part of the EU is regarded as favourable; but this is not so. In only two of the seven EU countries where the overall status of B. variegata was evaluated is its status favourable; in the other five the assessment is negative (European Environment Information and Observation Network, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Intensive agriculture is a major threat to biodiversity, and adds to the impermeability of the landscape, resulting in decreased migration potential [59]. Wider grass verges between fields and steppingstone biotopes between isolated populations more than 5 km apart [16] can help loosen up the landscape and make it more permeable for amphibians. An additional aspect is the embarkment of rivers.…”
Section: Discussionmentioning
confidence: 99%
“…A significant positive correlation between genetic and geographic distance was found in this study. A distance between 1 and 2 km is recommended for a good connectivity between subpopulations of the yellow-bellied toad [53], as well as the implementation of steppingstone biotopes in between subpopulations 5 or more km apart [16]. All these findings and recommendations emphasize the importance of short scale reestablishment of connectivity in the conservation of this species.…”
Section: Genetic Diversity and Population Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Higher genetic distances (F ST values) indicating population fragmentation have been found for amphibians (F ST = 0.32, N = 33 amphibian species) than for other taxa (e.g., F ST = 0.076 for birds and F ST = 0.26 for reptiles, [2]). For example, studies on the yellow-bellied toads Bombina variegata in Germany revealed highly structured populations with pairwise F ST values which were significantly different among most populations and an overall extremely low genetic diversity (as measured by heterozygosity, H O , H E and inbreeding F IS ) in most toad localities [24,25]. Other examples for highly structured amphibian species with low GD are the Oregon spotted frog Rana pretiosa from the Pacific Northwest [26], and the Arouss Al Ayn Salamandra inframaculata from northern Israel [27].…”
Section: Introductionmentioning
confidence: 99%